The Role of Law Enforcement in Ensuring the Rights of Citizens - Бакаянова, Нана Мезенівна; Бакаянова, Н. М.; Бакаянова, Нана Мезеновна; Bakaianova, Nana M.; Крижановська, Олена Володимирівна; Крижановська, О. В.; Крыжановская, Елена Владимировна; Kryzhanovska, Olena V.; Кубаєнко, Андрій Володимирович; Кубаєнко, А. В.; Кубаенко, Андрей Владимирович; Kubaienko, Andrii V. (ASERS Publishing, 2019)
The paper investigates human and citizen rights in Ukraine, their reflection in modern international regulations, in the laws of Ukraine. The features of the implementation of law enforcement in modern conditions are considered through the lens of the experience of other countries. The possibility of reforming the law enforcement system for improving its efficiency was analyzed. To achieve the purpose and form conclusions, various criteria for the effectiveness of law enforcement were considered. Particular importance in solving this issue was given to the analysis of foreign experience. The experience of other countries and world communities will allow to implement the best methods of law enforcement in Ukraine and improve its efficiency, paying particular attention to the rights of citizens even in high alert conditions (for example, in emergency situations, when human rights are minimized). Two leading approaches were used in the study: general theoretical and general historical. They helped identify the strengths and weaknesses of the current system in Ukraine and formulate specific positions for improving the activities of law enforcement agencies of Ukraine in protecting citizens' rights.

Стаття досліджує права людини та громадянина в Україні, їх відображення у сучасних міжнародних нормативних актах, у законодавстві України. Особливості перетворення правоохоронних органів у сучасних умовах розглядаються через призму досвіду інших країн. Проаналізовано можливість реформування правоохоронної системи для підвищення її ефективності. Для досягнення мети та формування висновків були розглянуті різні критерії ефективності правозастосування. Особливе значення у вирішенні цього питання надавалося аналізу зарубіжного досвіду. Досвід інших країн та світових спільнот дозволить впровадити найкращі методи правоохоронної діяльності в Україні та підвищити її ефективність, приділяючи особливу увагу правам громадян навіть в умовах підвищеної боєготовності (наприклад, у надзвичайних ситуаціях, коли права людини зводяться до мінімуму). У дослідженні використовувались два провідні підходи: загальнотеоретичний та загальноісторичний. Вони допомогли виявити сильні та слабкі сторони поточної системи в Україні та сформулювати конкретні позиції щодо вдосконалення діяльності правоохоронних органів України у захисті прав громадян.

Статья исследует права человека и гражданина в Украине, их отражение в современных международных нормативных актах, в законодательстве Украины. Особенности преобразования правоохранительных органов в современных условиях рассматриваются через призму опыта других стран. Проанализирована возможность реформирования правоохранительной системы для повышения ее эффективности. Для достижения цели и формирования выводов были рассмотрены различные критерии эффективности правоприменения. Особое значение в решении этого вопроса предавалось анализу зарубежного опыта. Опыт других стран и мировых сообществ позволит внедрить лучшие методы правоохранительной деятельности в Украине и повысить ее эффективность, уделяя особое внимание правам граждан даже в условиях повышенной боеготовности (например, в чрезвычайных ситуациях, когда права человека сводятся к минимуму). В исследовании использовались два ведущих подхода: общетеоретический и общеисторический. Они помогли выявить сильные и слабые стороны текущей системы в Украине и сформулировать конкретные позиции по совершенствованию деятельности правоохранительных органов Украины в защите прав граждан.
Bakaianova N. M. The Role of Law Enforcement in Ensuring the Rights of Citizens / N. M. Bakaianova, O. V. Kryzhanovska, A. V. Kubaienko // Journal of Advanced Research in Law and Economics. – V. 10 (8). – ASERS Publishing, 2019. – P. 2253 – 2261.
Keywords: law enforcement system; human rights; law enforcement agencies; reform; international organizations; правоохоронна система; права людини; правоохоронні органи; реформи; міжнародні організації; правоохранительная система; права человека; правоохранительные органы; реформа; международные организации; Research Subject Categories::LAW/JURISPRUDENCE